Influence of Corticospinal Tracts from Higher Order Motor Cortices on Recruitment Curve Properties in Stroke - Potter-Baker, Kelsey A.; Varnerin, Nicole M.; Cunningham, David A.; Roelle, Sarah M.; Sankarasubramanian, Vishwanath; Bonnett, Corin E.; Machado, Andre G.; Conforto, Adriana B.; Sakaie, Ken; Plow, Ela B. (Frontiers in Neuroscience, 2016)
BACKGROUND: Recruitment curves (RCs) acquired using transcranial magnetic stimulation are commonly used in stroke to study physiologic functioning of corticospinal tracts (CST) from M1. However, it is unclear whether CSTs from higher motor cortices contribute as well. OBJECTIVE: To explore whether integrity of CST from higher motor areas, besides M1, relates to CST functioning captured using RCs. METHODS: RCs were acquired for a paretic hand muscle in patients with chronic stroke. Metrics describing gain and overall output of CST were collected. CST integrity was defined by diffusion tensor imaging. For CST emerging from M1 and higher motor areas, integrity (fractional anisotropy) was evaluated in the region of the posterior limb of the internal capsule, the length of CST and in the region of the stroke lesion. RESULTS: We found that output and gain of RC was related to integrity along the length of CST emerging from higher motor cortices but not the M1. CONCLUSIONS: Our results suggest that RC parameters in chronic stroke infer function primarily of CST descending from the higher motor areas but not M1. RCs may thus serve as a simple, in-expensive means to assess re-mapping of alternate areas that is generally studied with resource-intensive neuroimaging in stroke.